2022
DOI: 10.3390/ijerph19169961
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Gut Microbiome and Pathologies in Pregnancy

Abstract: Pregnancy is a special period in a woman’s life when her organism undergoes multiple physiological changes so that the fetus has optimal conditions for growth and development. These include modifications in the composition of the microbiome that occur between the first and third trimesters of pregnancy. There is an increase in Akkermansia, Bifidobacterium, and Firmicutes, which have been associated with an increase in the need for energy storage. The growth in Proteobacteria and Actinobacteria levels has a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 136 publications
(162 reference statements)
0
35
0
2
Order By: Relevance
“…One observational study found an association between vitamin D dietary intake and a reduction of microbiome richness, and an increase of bacteria with proinflammatory properties [22], however, due to the lack of serum vitamin D level measurements, and considering that its absorption may depend on many factors other than only diet, the knowledge gap persists. Changes in the maternal gut microbiome are known to be associated with the development of preeclampsia, gestational diabetes and other serious pregnancy pathologies [23] and with negative offspring outcomes, especially with those related to immunity or allergic diseases [24][25][26]. Thus, exploring the effects of maternal vitamin D status on their microbiome is not only useful to identify potential associated pregnancy complications or impacts on the mothers' health.…”
Section: Introductionmentioning
confidence: 99%
“…One observational study found an association between vitamin D dietary intake and a reduction of microbiome richness, and an increase of bacteria with proinflammatory properties [22], however, due to the lack of serum vitamin D level measurements, and considering that its absorption may depend on many factors other than only diet, the knowledge gap persists. Changes in the maternal gut microbiome are known to be associated with the development of preeclampsia, gestational diabetes and other serious pregnancy pathologies [23] and with negative offspring outcomes, especially with those related to immunity or allergic diseases [24][25][26]. Thus, exploring the effects of maternal vitamin D status on their microbiome is not only useful to identify potential associated pregnancy complications or impacts on the mothers' health.…”
Section: Introductionmentioning
confidence: 99%
“…One observational study found an association between vitamin D dietary intake and a reduction of microbiome richness and an increase of bacteria with proinflammatory properties [22]; however, due to the lack of serum vitamin D level measurements, and considering that its absorption may depend on many factors other than only diet, the knowledge gap persists. Changes in the maternal gut microbiome are known to be associated with the development of preeclampsia, gestational diabetes, and other serious pregnancy pathologies [23] and with negative offspring outcomes, especially with those related to immunity or allergic diseases [24][25][26]. Thus, exploring the effects of the maternal vitamin D status on their microbiome is not only useful in identifying potential associated pregnancy complications or impacts on the mother's health.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors, such as maternal obesity, diet, and physical activity; pregnancy-related factors, such as excessive fat storage and increased secretion of adipokine and cytokines (e.g., tumor necrosis factor-α(TNF-α) and interleukin-6(IL-6)) [ 5 ]; and genetics also contribute to the development of IR in pregnancy [ 3 ]. A large amount of scientific data from the last two decades has also indicated the role of gut microbiota in the development of gestational glucose intolerance during pregnancy [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%